Analisis Korelasi HbA1c dengan Mean Platelet Volume dan Platelet Distribution Width pada Pasien Diabetes Melitus Tipe 2 - Azzahra, Andi Dinda; Anhar, Citra Amaniah; Hardianto, Nova (Jurnal Laboratorium Khatulistiwa, 2025)
Controlling blood glucose levels is the main key in treating and preventing diabetic vascular complications. However, routine monitoring of glycemic status using standard HbA1c markers is still hampered by limited costs and health facilities. The platelet index is considered to have potential as a predictor of vascular complications in DM patients. This study aims to examine the correlation of HbA1c with mean platelet volume (MPV) and platelet distribution width (PDW) in type 2 DM patients. This cross-sectional study used medical record data. The sample consisted of 60 patients with type 2 diabetes who received treatment at Pasar Rebo Regional General Hospital, Jakarta, in 2024. All patients had HbA1c levels above 6.5%. The proportion of patients with high MPV and PDW was 5% and 11.7%, respectively. Based on bivariate analysis with the Spearman test, there was a significant correlation between HbA1c levels and MPV values (p-value < 0.05; r = 0.561) and PDW values (p-value < 0.05; r = 0.433). A strong positive correlation was observed between HbA1c levels and MPV values and a moderate positive correlation between HbA1c levels and PDW values, indicating that an increase in HbA1c levels tends to be accompanied by an increase in MPV and PDW values.